‘A Beginner Foreigner’: Early Experiences of Migrant Learners in Schools in South Africa - Jude Ifeanyichukwu Nnadozie; Pholoho Justice Morojele (International Journal of Social Sciences & Educational Studies, 2023)
In recent years, South Africa has been a primary destination for African migrants. Many of the migrants are with their families. This implies that there are many migrant children in South African schools. Studies on migration and migrants’ experiences in their host countries have not paid adequate attention on the schooling experiences of migrant children in their destination countries. This paper examined the early experiences of migrant learners in South Africa. It focuses on migrant learners from the Democratic Republic of Congo (DRC) and Zimbabwe in Durban, South Africa. The study employed qualitative research approach and narrative inquiry methodology. Data was collected using story account, open ended interview and photo voice. The findings reveal that among the challenges and limitations migrant learners encounter on their arrival in South Africa are issues such as difficulty in accessing education as a result of immigration documentation, language barrier and cultural alienation in school.